2023
DOI: 10.1101/2023.04.05.535794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of subunit selective substrates forTrichomonas vaginalisproteasome

Abstract: The protozoan parasite, Trichomonas vaginalis (Tv) causes trichomoniasis, the most common, non-viral, sexually transmitted infection in the world. Only two closely related drugs are approved for its treatment. The accelerating emergence of resistance to these drugs and lack of alternative treatment options poses an increasing threat to public health. There is an urgent need for novel effective anti-parasitic compounds. The proteasome is a critical enzyme for T. vaginalis survival and was validated as a drug ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Notably, the background was less pronounced with LJL-1 and LJL-2 compared to that with Me 4 BodipyFL-Ahx 3 L 3 VS. Previous research using purified Tv20S identified the electrophoretic migration order of the β subunits as β2, β1, and β5, from highest to lowest molecular weight . Accordingly, we wished to employ inhibitors that selectively inactivate one or other β subunit such that the uninhibited subunit(s) would be available to bind to the probe.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, the background was less pronounced with LJL-1 and LJL-2 compared to that with Me 4 BodipyFL-Ahx 3 L 3 VS. Previous research using purified Tv20S identified the electrophoretic migration order of the β subunits as β2, β1, and β5, from highest to lowest molecular weight . Accordingly, we wished to employ inhibitors that selectively inactivate one or other β subunit such that the uninhibited subunit(s) would be available to bind to the probe.…”
Section: Resultsmentioning
confidence: 99%
“…Lysate (16 μg) was preincubated with (1) DMSO, (2) 20 μM E64, (3) 2 mM PMSF or (4) 10 μM MZB, prior to addition of probe. (B) Schematic of inhibitor or inhibitor combinations known to inhibit one or more Tv20S β subunits . (C) Fluorescence imaging of Tv20S β subunits after incubation with β subunit-specific inhibitors or combinations of inhibitors, and enrichment from parasite lysate using the biotin functionality of LJL-2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations